Teachers Reflection on their Preparedness for Teaching English to Young Learners Using Online Method - Widie Maulidyawati; Dwiniasih Dwiniasih; Jaufillaili Jaufillaili; Takad Ahmed Chowdhury (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2021)
Since the COVID-19 pandemic disrupted people's normal lives across the globe, educational institutions have been compelled to embrace virtual learning. This mixed-method study aimed to investigate the teachers preparedness for online teaching at an elementary school in West Java in Indonesia and to find out the challenges they face while teaching young learners. It employed a close ended questionnaire followed by interviews to collect necessary data from seven purposively selected English language teachers based on their availability and experience in online teaching. The data demonstrated that most of the teachers in the context were well prepared to teach online. The findings entailed their mastery of necessary technical skills, prior experience and responsiveness with online teaching, commitment to carry out their duties as teachers and efficiency in time management in online teaching. However, the results also revealed a number of issues from some respondents such as limited knowledge in using different virtual media, high internet cost, lack of support from the education department, unstable internet connectivity, limited cellular broadband data, lack of skills in navigating available technology, inadequate knowledge of internet technology, unfamiliarity with online resources, and insufficient training. The research will help English language teachers, educational policymakers, and other stakeholders adopt more successful online education.